Metal organic structure and method for manufacturing same
By applying centrifugal force and shear force, or pre-particulate multi-dentate ligand and then applying centrifugal force and shear force, the problems of long MOF synthesis time and insufficient monodispersible fluidity in the prior art are solved, and excellent MOF particles are successfully manufactured.
Patent Information
- Application Number
- CN202380048166.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-04
- Filing Date
- 2023-07-04
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to synthesize high-quality metal organic structures (MOFs) in a short reaction time, and their monodispersity and fluidity are insufficient.
By repeatedly applying centrifugal force and shear force, or pre-particulate multi-dentate ligand and then applying centrifugal force and shear force, MOF particles having a volume average particle size of 1.0 μm or more and 30.0 μm or less, and a ratio of D10/D90 to particle size D90 is produced.
It is possible to produce MOF particles with excellent monodispersity and flowability, and their size can be freely controlled during subsequent processing.
Smart Images

Figure CN119546567A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metal organic structure and a method for manufacturing the same. Background Art
[0002] In recent years, as a decarbonization measure, the use of various gases with less environmental impact than petroleum has been promoted. Among them, in the fields of gas storage and gas separation, a group of materials called metal organic frameworks (MOFs) or porous coordination polymers (PCPs) have attracted attention. Metal organic frameworks are compounds with a structure in which metal atoms are cross-linked by organic ligands, and are typically porous.
[0003] As the manufacturing method of metal organic structure, typically use liquid phase synthesis methods such as solution stirring method, hydrothermal synthesis method, solvent thermal synthesis method, microwave irradiation method, electrolytic synthesis method, flow reactor synthesis method, spray drying synthesis method and ultrasonic irradiation method. In addition, sometimes use solid phase synthesis method using mortar, ball mill device etc. In addition, in recent years, also reported the method of synthesizing metal organic structure using twin screw mixing device called extruder. However, when using the aforementioned methods, it is sometimes difficult to synthesize high quality metal organic structure in a shorter reaction time.
[0004] Therefore, Patent Document 1 proposes a method for producing high-quality MOF in a short time by applying centrifugal force and shear force to a mixture obtained by mixing a metal ion donor, a multidentate ligand, and a solvent as raw materials.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent document 1: EP3971160A1 Summary of the invention
[0008] As a method for utilizing the manufactured MOF, a variety of methods have been proposed, such as processing granular MOF as a raw material into a shaped body such as a pellet or a sheet and using it as an adsorbent, requiring a MOF with higher processability. When the granular MOF is processed into a shaped body, it is ideal for the MOF to be a microparticle from the viewpoint of processability. In addition, in order to improve the filling property when processed into a shaped body, a monodisperse and highly fluid MOF is ideal. Therefore, the MOF manufactured by the existing method described in Patent Document 1 has room for improvement in terms of monodispersity and fluidity.
[0009] Therefore, an object of the present invention is to provide MOF particles which are fine particles and have a narrow particle size distribution and are excellent in monodispersity and fluidity.
[0010] In order to solve the above-mentioned problems, the present inventors conducted intensive research and found that by repeatedly applying centrifugal force and shear force, or by pre-micronizing the multidentate ligand as a raw material and then applying centrifugal force and shear force, MOF particles with a narrow particle size distribution can be produced.
[0011] That is, the present invention provides a metal organic structure having a volume average particle size of 1.0 μm or more and 30.0 μm or less.
[0012] Particle size D 10 Relative to particle size D 90 Ratio D 10 / D 90 It is 0.35 or more and 1.00 or less.
[0013] In addition, the present invention provides a method for producing a metal organic structure, which comprises a centrifugal shearing step of simultaneously applying centrifugal force and shear force to a mixture containing a metal ion donor, a multidentate ligand and a solvent,
[0014] The method for producing a metal-organic structure includes a step of recovering the mixed material supplied to the centrifugal shearing step and supplying the mixed material to the centrifugal shearing step again.
[0015] Furthermore, the present invention provides a method for producing a metal organic structure, which comprises a centrifugal shearing step of simultaneously applying centrifugal force and shear force to a mixture comprising a metal ion donor, a multidentate ligand and a solvent, wherein:
[0016] The median particle size D of the multidentate ligand is 50 It is not less than 0.1 μm and not more than 50.0 μm. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a diagram showing the X-ray diffraction (XRD) pattern of the MOF obtained in Example 3.
[0018] Figure 2 This is a diagram showing the X-ray diffraction (XRD) pattern of MOF obtained in Comparative Example 2.
[0019] Figure 3 This is a diagram showing the X-ray diffraction (XRD) pattern of MOF obtained in Example 11. DETAILED DESCRIPTION
[0020] Hereinafter, the present invention will be described based on preferred embodiments thereof.
[0021] The volume average particle size of the metal organic structure (hereinafter sometimes referred to as "MOF") of the present invention is 1.0 μm or more and 30.0 μm or less. 10 Relative to particle size D 90 Ratio D 10 / D 90 is greater than 0.35 and less than 1.00. Since MOF has the above-mentioned characteristics, the particles of the MOF have excellent monodispersity and excellent fluidity. In addition, since the particles are micronized, the size can be freely controlled when granulating or making any structure.
[0022] From the viewpoint of operability when processing the micronized and granular MOF into a molded body, the volume average particle size is preferably 1.5 μm or more, more preferably 2.0 μm or more, further preferably 2.5 μm or more, and most preferably 3.0 μm or more. From the same viewpoint, the volume average particle size is preferably 20.0 μm or less, more preferably 15.0 μm or less, further preferably 10.0 μm or less, further preferably 8.0 μm or less, and most preferably 6.0 μm or less.
[0023] From the viewpoint of monodispersity and fluidity, the particle size D 10 Relative to particle size D 90 Ratio D 10 / D 90 It is preferably 0.37 or more and 1.00 or less, and more preferably 0.40 or more and 1.00 or less. 10 / D 90 When the value is close to 1, the particle size distribution of MOF becomes narrower, so not only the monodispersity but also the fluidity is improved.
[0024] Volume average particle size, D 10 and D 90 It can be obtained by, for example, a laser diffraction scattering particle size distribution measurement method. The volume average particle size is a value obtained by a laser diffraction scattering particle size distribution measurement method. Suppose there is a powder group in which, in order from small to large, there are n1, n2, ..., ni, ..., nk particles with particle sizes d1, d2, ..., di, ..., dk, respectively. In addition, let the surface area of each particle be ai, and the volume be vi. At this time, the volume average particle size MV weighted by volume is calculated using the following formula (see Microtrac (MT3000) operating instructions from MicrotracBEL). D 10 and D 90 The volume cumulative particle diameters at the cumulative volumes of 10% by volume and 90% by volume are obtained by laser diffraction scattering particle size distribution measurement method.
[0025] MV=(v1×d1+v2×d2+……+vi×di+……+vk×dk) / (v1+v2+……+vi+……vk)
[0026] From the perspective of micronization, in the MOF of the present invention, the volume frequency of particles with a particle size of less than 2 μm is preferably 20% or less, more preferably 15% or less, and further preferably 10% or less. By satisfying the above conditions, high fluidity can be ensured. The lower limit of the volume frequency is not particularly limited, but is typically 0% or more.
[0027] For the MOF of the present invention, the angle of repose is preferably 50° or less, more preferably 45° or less, and further preferably 40° or less. The angle of repose has a small value as described above, thereby ensuring high fluidity of the MOF. The lower limit of the angle of repose is not particularly limited, but is typically 0° or more.
[0028] The angle of repose refers to the angle between the slope of a mountain formed when the MOF is allowed to fall freely from a certain height and remains stable without spontaneously collapsing, and the horizontal plane.
[0029] The repose angle of the MOF of the present invention can be measured in the following manner, that is, using a repose angle measuring device consisting of a funnel and a measuring table, allowing the MOF to fall freely and measuring the angle of the powder after falling. Specifically, a sample is added from a funnel with a height of 40 mm (funnel aperture: 5 mm, funnel angle: 60°) to a measuring table (measuring table diameter: 30 mm), and when the sample is dripped from a height of 40 mm to the measuring table, the sample is stopped when the sample overflows from the measuring table and falls to the surroundings, and the angle between the measuring table and the powder is measured 3 times with a protractor, and the average value can be used as the measured value.
[0030] In addition, the compression degree of the MOF of the present invention is preferably less than 50%, more preferably less than 45%, further preferably less than 40%, and most preferably less than 35%. The compression degree is the value obtained by dividing the difference between the bulk density and the tap density by the tap density. When the fluidity is high, the difference between the bulk density and the tap density becomes smaller and the compression degree tends to become smaller. The compression degree of the MOF of the present invention has a low value as described above, so the high fluidity of the MOF can be ensured.
[0031] The degree of compression can be calculated by dividing the difference between the bulk density and the tap density by the tap density.
[0032] The bulk density can be determined by dropping the MOF from a funnel into a cup of any volume and scraping off the excess before measuring the weight. The tapped density can be determined by tapping the cup several times under certain conditions until the volume of the powder in the cup becomes constant and then measuring the volume and weight of the powder. Specifically, the sample is dropped from a 40 mm high funnel (funnel aperture: 5 mm, funnel angle: 60°) into a cup (capacity: 25 cm 3 ) until it overflows from the cup, then use a metal scraper to scrape off the excess overflow from the cup horizontally. The weight of the sample in the cup can be measured and divided by the cup capacity (25cm 3 ) to calculate the density. The density can be measured three times and the average value is taken as the bulk density.
[0033] The tap density can be calculated by placing 5 g of sample in a measuring cylinder, tapping it repeatedly from a height of 4 cm until the scale position of the powder becomes constant, and dividing the sample weight when the scale position becomes constant by the sample volume confirmed by the scale.
[0034] The BET specific surface area of the MOF of the present invention is preferably 100 m 2 / g and above 10000m 2 / g or less, more preferably 200m 2 / g and above and 5000m 2 / g or less, more preferably 500m 2 / g and above 4000m 2 / g or less, more preferably 1000m 2 / g and above 2300m 2 / g or less, and more preferably 1650m 2 / g and above 2300m 2 / g or less, and most preferably 1700m 2 / g and above 2300m 2 By making MOF have such a high specific surface area, for example, MOF can store a large amount of gas in gas storage applications, and can exhibit excellent characteristics in various applications.
[0035] MOFs contain metal ion donors and multidentate ligands.
[0036] Examples of metal elements constituting the metal ion donor include any element belonging to alkali metals (Group 1), alkaline earth metals (Group 2), transition metals (Groups 3 to 12), Group 13 elements, and rare earth elements (atomic numbers 21, 29, 57 to 71). The metal element typically includes at least one selected from copper, iron, zinc, zirconium, aluminum, cobalt, magnesium, nickel, chromium, hafnium, and lanthanum. That is, the metal ion donor includes ions of these metal elements, that is, at least one metal ion selected from copper ions, iron ions, zinc ions, zirconium ions, aluminum ions, cobalt ions, magnesium ions, nickel ions, chromium ions, hafnium ions, and lanthanum ions.
[0037] The aforementioned metal ions are typically hexacoordinated or tetracoordinated. In the case where the metal ion is hexacoordinated, from the viewpoint of smoothly synthesizing MOF, it is preferred to use a bidentate ligand as the multidentate ligand described below. From the same viewpoint, in the case where the metal ion is tetracoordinated, it is preferred to use a tridentate ligand as the multidentate ligand described below.
[0038] As the metal ion donor, a metal salt is typically used. The metal ion donor may be an organic salt or an inorganic salt. The metal ion donor is typically selected from the group consisting of hydroxide salts, carbonates, acetates, sulfates, nitrates and chloride salts. A plurality of metal ion donors containing the same metal element may be used in combination.
[0039] The multidentate ligand is typically an organic multidentate ligand, for example, selected from a group consisting of carboxylic acid anions, amine compounds, sulfonic acid anions, phosphate anions, and heterocyclic compounds. As carboxylic acid anions, for example, can be cited: anions of at least one organic compound selected from trimesic acid (BTC), terephthalic acid (BDC), isophthalic acid, 2-methylimidazole, 2-5-dihydroxyterephthalic acid (dobdc or DHTA), 4,4'-dioxy anion base-3,3'-biphenyl dicarboxylate anion (dobpdc), fumaric acid, formic acid, 1,3,5-tris (4-carboxyphenyl) benzene (BTB), 4,4'-biphenyl dicarboxylic acid (BPDC), oxalic acid, 1,2,4-triazole, and 3,5-pyrazole dicarboxylic acid (H3PDC). In this case, by combining the aforementioned metal ions with the aforementioned multidentate ligands, a MOF having various characteristics such as biocompatibility, catalytic properties, photoresponsiveness, and semiconductor properties can be prepared.
[0040] The combination of metal ions and multidentate ligands contained in the MOF of the present invention, and the MOF containing the combination are not particularly limited, and preferably are: Al(OH)(bpdc) containing Al and BPDC, CAU-10 containing Al and isophthalic acid, CAU-4 containing Al and BTB, MIL-100Al containing Al and BTC, MIL-53Al containing Al and BDC, MIL-53-Fum containing Al and fumaric acid, MOF-303 containing Al and H3PDC, ZIF-67 containing Co and 2-methylimidazole, MOF-74Co containing Co and dopdc, MIL-101Cr containing Cr and BDC, Cu(H2O)(1,3-BDC containing Cu and isophthalic acid, MIL-100Al containing Al and BTC, MIL-53Al containing Al and BDC, MIL-53-Fum containing Al and fumaric acid, MOF-303 containing Al and H3PDC, ZIF-67 containing Co and 2-methylimidazole, MOF-74Co containing Co and dopdc, MIL-101Cr containing Cr and BDC, Cu(H2O)(1,3-BDC containing Cu and isophthalic acid, M OF-199, MIL-100Fe comprising Fe and BTC, MIL-53Fe comprising Fe and BDC, MIL-88B comprising Fe and BDC, La-BTB comprising La and BTB, MOF-274 comprising Mg and dopdc, MOF-74Mg comprising Mg and dopdc, Mg-formate comprising Mg and formic acid, CALF-20 comprising Zn and oxalic acid, MOF-177 comprising Zn and BTB, MOF-5 comprising Zn and BDC, MOF-74Zn comprising Zn and dopdc, ZIF-8 comprising Zn and 2-methylimidazole, MOF-801 comprising Zr and fumaric acid, UiO-66 comprising Zr and BDC, and MOF-74Ni comprising Ni and dopdc.
[0041] Next, a suitable method for producing the MOF of the present invention will be described.
[0042] First, a mixture comprising a metal ion donor, a multidentate ligand and a solvent is prepared. The metal ion donor and the multidentate ligand use substances such as those described above. The solvent is not particularly limited, and a solvent commonly used for synthesizing metal organic structures can be used. However, the aforementioned solvent is preferably a poor solvent relative to at least one of the metal ion donor and the multidentate ligand. When such a composition is adopted, the mixture cannot form a complete solution, but forms a semi-solid state with a solid component remaining, typically in a slurry state. Thus, the centrifugal force and shear force described later can be applied to the aforementioned mixture more effectively.
[0043] Here, a solvent being a "poor solvent" for a certain object means that the solubility of the aforementioned object in the aforementioned solvent is 1 g / 50 mL (= 20 g / L) or less at 25°C and atmospheric pressure. Examples of usable solvents include: water; alcohols such as methanol and ethanol; carboxylic acids such as formic acid and acetic acid; amides such as N,N-dimethylformamide (DMF) and N,N-diethylformamide (DEF); and esters such as ethyl acetate. A mixture of multiple solvents may also be used.
[0044] The amount of the solvent is set to, for example, 100% by mass or more, preferably 200% by mass or more, based on the total amount of the metal ion donor and the multidentate ligand.
[0045] The amount of the solvent is set to, for example, 1000 mass % or less, preferably 700 mass % or less, and more preferably 500 mass % or less, based on the total amount of the metal ion donor and the multidentate ligand.
[0046] When such a configuration is adopted, for example, in addition to being able to improve the efficiency of MOF production, when an organic solvent is used, the environmental burden can be reduced by reducing the amount of solvent used.
[0047] The aforementioned mixture may further include supplementary substances such as reaction accelerators. The reaction accelerator is, for example, an alkaline substance or an acidic substance, typically an alkaline substance. As the alkaline substance, for example, diethylamine, triethylamine, 2,6-lutidine, pyridine, imidazole, potassium hydroxide and sodium hydroxide can be mentioned. As the acidic substance, for example, formic acid, acetic acid, trifluoroacetic acid, sulfuric acid, nitric acid, hydrochloric acid and phosphoric acid can be mentioned. As a supplementary substance, a variety of reaction accelerators can be used in combination. As a supplementary substance, a reaction control agent can also be added.
[0048] The aforementioned compound is simultaneously and continuously subjected to centrifugal force and shear force and mixed. The mixture obtained by mixing is recovered, and centrifugal force and shear force are applied again and mixed. Thus, MOF can be manufactured in a short time and with high quality, and the above-mentioned monodisperse and high-fluidity MOF can be successfully obtained.
[0049] As a method for simultaneously and continuously applying centrifugal force and shear force, for example, the following method can be cited. First, the mixture is introduced into a reaction vessel. Then, the rotary blades provided by the reaction vessel are rotated to stir the mixture at high speed. Through this rotation operation, centrifugal force is imparted to the mixture, and the mixture is pressed against the inner wall of the reaction vessel. In this way, the mixture contacts the inner wall of the reaction vessel, and centrifugal force and shear force are simultaneously and continuously applied to the mixture. In this state, the high energy generated by the shear force is imparted to the mixture, and the metal ion donor in the mixture reacts with the multidentate ligand to obtain MOF. The shear force can also be generated by the particles constituting the mixture contacting each other.
[0050] As an example of the above method, there can be cited the thin film gyratory mixing method developed by PRIMIX Co., Ltd. This method uses a thin film gyratory high-speed mixer to simultaneously and continuously apply centrifugal force and shear force to the introduced substance. The specific device structure is disclosed in, for example, JP2007-125454A.
[0051] As a method for recovering the mixture obtained by the above method and mixing it again by applying centrifugal force and shear force, in addition to the intermittent method as literally described, in which the mixture is recovered from the above mixer and the mixture is reintroduced into the mixer, there can be mentioned: a circulation method (continuous method) in which a circulation pipe and a pump are provided in the mixer, the mixture is recovered from the mixer, and the recovered mixture is continuously introduced into the mixer via the circulation pipe.
[0052] When the recovered mixture is introduced into the mixer again and centrifugal force and shear force are applied again, the number of times of the process of applying centrifugal force and shear force is more than 2 times, preferably more than 3 times and less than 10 times, more preferably more than 3 times and less than 8 times, and more preferably more than 3 times and less than 5 times. Thus, the MOF of the present invention with excellent monodispersity and fluidity can be obtained smoothly. In the case where the recovery of the mixture is cyclic (continuous), the above-mentioned number of times refers to the number of times calculated by dividing the time the mixer is operated by the time the slurry passes through the reaction vessel once. The time the slurry passes through the reaction vessel once can be calculated by dividing the volume (L) of the slurry by the flow rate (L / minute) of the slurry.
[0053] In both the intermittent and circulating (continuous) processes, the time for applying centrifugal force and shear force to the mixture is not particularly limited and can be appropriately adjusted according to the capacity of the reaction container, the capacity of the mixture, the flow rate of the slurry, and the peripheral speed of the rotating blades.
[0054] In addition, in the method for producing MOF of the present invention, when centrifugal force and shear force are simultaneously and continuously applied to the aforementioned mixed materials and mixed, the obtained mixture is recovered and centrifugal force and shear force are applied again to mix. In addition to or on this basis, the raw materials are pre-micronized to successfully obtain the above-mentioned monodisperse and high-fluidity MOF.
[0055] In this case, in the above compound, the median particle size D of the multidentate ligand is 50 The diameter is preferably set to 0.1 μm or more, more preferably 1.0 μm or more, further preferably 5.0 μm or more, further preferably 10.0 μm or more, and particularly preferably 20.0 μm or more.
[0056] In addition, it is preferred that the median particle size D of the multidentate ligand be 50 It is 130 μm or less, more preferably 80.0 μm or less, further preferably 50.0 μm or less, further preferably 40.0 μm or less, and particularly preferably 30.0 μm or less.
[0057] Similarly, the median particle size D 50Although not particularly limited, for example, it is preferably set to 1.0 μm or more, more preferably 5.0 μm or more, and even more preferably 10.0 μm or more.
[0058] In addition, the median particle size D of the metal ion donor 50 For example, it is preferably set to 50.0 μm or less, more preferably 30.0 μm or less, and further preferably 20.0 μm or less.
[0059] These median particle sizes are the volume cumulative particle sizes at 50% volume obtained by laser diffraction scattering particle size distribution measurement. 10 and D 90 Similarly, it can be determined by laser diffraction scattering particle size distribution measurement.
[0060] When the MOF is produced using the micronized raw material as described above, the number of steps of applying the centrifugal force and the shear force is preferably 1 or more and 10 or less, more preferably 2 or more and 10 or less, further preferably 3 or more and 10 or less, and most preferably 3 or more and 5 or less. Thus, the coarse raw material can be crushed in advance, so that the MOF of the present invention having excellent monodispersity and fluidity can be obtained smoothly. The above number of times can be calculated as described above.
[0061] In addition, in the above-mentioned manufacturing method, the circumferential speed of the rotating blade is preferably 10 m / s or more and 100 m / s or less, more preferably 20 m / s or more and 80 m / s or less, further preferably 20 m / s or more and 60 m / s or less, and further preferably 20 m / s or more and 40 m / s or less in both methods. Thus, the MOF having excellent monodispersity and fluidity of the above-mentioned present invention can be obtained smoothly.
[0062] As mentioned above, although this invention was demonstrated based on these preferred embodiments, this invention is not limited to the said embodiment.
[0063] The present invention includes the following embodiments.
[0064] [1] A metal organic structure having a volume average particle size of 1.0 μm or more and 30.0 μm or less,
[0065] Particle size D 10 Relative to particle size D 90 Ratio D 10 / D 90 It is 0.35 or more and 1.00 or less.
[0066] [2] The metal-organic structure according to [1], wherein the volume frequency of particles having a particle size of less than 2 μm is 20% or less.
[0067] [3] The metal-organic structure according to [1] or [2], wherein the angle of repose is 50° or less.
[0068] [4] The metal-organic structure according to any one of [1] to [3], wherein the degree of compression is 50% or less.
[0069] [5] The metal-organic structure according to any one of [1] to [4], comprising at least one metal ion selected from the group consisting of alkali metal ions, alkaline earth metal ions, transition metal ions, Group 13 element ions, and rare earth element ions.
[0070] [6] The metal-organic structure according to [5], wherein the metal ion includes at least one metal ion selected from the group consisting of copper ion, iron ion, zinc ion, zirconium ion, aluminum ion, cobalt ion, magnesium ion, calcium ion, nickel ion, chromium ion, hafnium ion and lanthanum ion.
[0071] [7] The metal-organic structure according to any one of [1] to [6], which comprises at least one organic compound selected from trimesic acid (BTC), terephthalic acid (BDC), isophthalic acid, 2-methylimidazole, 2-5-dihydroxyterephthalic acid (dobdc or DHTA), 4,4'-dioxyanion-3,3'-biphenyldicarboxylate anion (dobpdc), fumaric acid, formic acid, 1,3,5-tris(4-carboxyphenyl)benzene (BTB), 4,4'-biphenyldicarboxylic acid (BPDC), oxalic acid, 1,2,4-triazole and 3,5-pyrazoledicarboxylic acid (H3PDC).
[0072] [8] The metal organic structure according to any one of [1] to [7], wherein the BET specific surface area is 100 m 2 / g and above 10000m 2 / g or less.
[0073] [9] A method for producing a metal organic structure, comprising a centrifugal shearing step of simultaneously applying centrifugal force and shear force to a mixture containing a metal ion donor, a multidentate ligand and a solvent,
[0074] The method for producing a metal-organic structure includes a step of recovering the mixed material supplied to the centrifugal shearing step and supplying the mixed material to the centrifugal shearing step again.
[0075]
[10] The method for producing a metal-organic structure according to [9], wherein the centrifugal shearing step is performed 3 or more times and 10 or less times.
[0076]
[11] A method for producing a metal organic structure, comprising a centrifugal shearing step of simultaneously applying centrifugal force and shear force to a mixture comprising a metal ion donor, a multidentate ligand and a solvent, wherein:
[0077] The median particle size D of the multidentate ligand is 50 It is not less than 0.1 μm and not more than 50.0 μm.
[0078]
[12] The method for producing a metal-organic structure according to
[11] , wherein the number of times of the centrifugal shearing step is 1 or more and 10 or less.
[0079]
[13] The method for producing a metal-organic structure according to any one of [9] to
[12] , wherein the centrifugal shearing step uses a reaction vessel equipped with a rotary blade, and the circumferential speed of the rotary blade is greater than or equal to 10 m / s and less than or equal to 100 m / s.
[0080] Example
[0081] (Examples 1 and 2)
[0082] Using copper hydroxide (Cu(OH)2) as a metal ion donor, using trimesic acid (BTC) as a multidentate ligand, and using methanol as a solvent, they are put into a thin film gyratory high-speed mixer (manufactured by PRIMIX Co., Ltd.), and the mixture is recovered from the mixer, and the mixture is introduced into the mixer again to manufacture MOF in an intermittent manner. The obtained MOF is washed with methanol and dried at 50°C in a vacuum dryer for a certain period of time. The obtained MOF is analyzed by X-ray diffraction (XRD), and the result is Cu3(BTC)2·H2O. The measurement conditions of XRD are shown below.
[0083] <X-ray diffraction measurement conditions>
[0084] ·Device used: MiniFlex manufactured by Rigaku Corporation
[0085] Tube: CuKα ray
[0086] ·Measurement of diffraction angle: 2θ = 2 to 80°
[0087] ·Measurement step: 0.02°
[0088] The median particle size D of the BTC used 50 , the total amount (powder amount) of copper hydroxide and BTC, and the amount of methanol used are shown in Table 1. In addition, the peripheral speed, operation mode and number of repeated introductions of the above-mentioned mixer are also shown in Table 1. Furthermore, the volume average particle size and particle size D 10 Relative to particle size D 90 Ratio D10 / D 90 The volume frequency of particles with a volume average particle size of less than 2 μm and the BET specific surface area are also shown in Table 1. 10 / D 90 , volume frequency of particles with a volume average particle size of less than 2 μm, and BET specific surface area measurement conditions. In this example, the angle of repose and compression were not measured, so they are indicated by "-" in the table.
[0089] <Volume average particle size measurement conditions>
[0090] ·Device used: MT3000 manufactured by MicrotracBEL Co., Ltd.
[0091] Pretreatment conditions: Ultrasonic power 40W, ultrasonic time 180 seconds, degassing treatment
[0092] Particle size distribution: volume conversion
[0093] · Refractive index of particles: 1.81
[0094] ·Measurement solvent (refractive index): water (1.333)
[0095] <Compared to D 10 / D 90 Measurement conditions>
[0096] ·Device used: MT3000 manufactured by MicrotracBEL Co., Ltd.
[0097] Pretreatment conditions: Ultrasonic power 40W, ultrasonic time 180 seconds, degassing treatment
[0098] Particle size distribution: volume conversion
[0099] · Refractive index of particles: 1.81
[0100] ·Measurement solvent (refractive index): water (1.333)
[0101] <Conditions for measuring volume frequency of particles with a volume average particle size of less than 2 μm>
[0102] ·Device used: MT3000 manufactured by MicrotracBEL Co., Ltd.
[0103] Pretreatment conditions: Ultrasonic power 40W, ultrasonic time 180 seconds, degassing treatment
[0104] Particle size distribution: volume conversion
[0105] Particle refractive index: 1.81
[0106] ·Measurement solvent (refractive index): water (1.333)
[0107] <BET specific surface area>
[0108] ·Device used: BELSORP-mini manufactured by MicrotracBEL Co., Ltd.
[0109] Pretreatment conditions: temperature 150°C, holding time 3 hours, vacuum exhaust treatment
[0110] Adsorbate: Nitrogen
[0111] Adsorption temperature: 77.35K
[0112] Analytical conditions: BET method (Type I, ISO9277)
[0113] (Examples 3 to 7)
[0114] Copper hydroxide (Cu(OH)2) was used as a metal ion donor, trimesic acid (BTC) was used as a multidentate ligand, and methanol was used as a solvent. These were placed in a thin film gyratory high-speed mixer (manufactured by PRIMIX Co., Ltd.). MOF was manufactured in the same manner as in Example 1, except that a circulation method (continuous method) was used, i.e., the recovered mixture was continuously introduced from the upper part of the mixer. The obtained MOF was washed and dried. The obtained MOF was analyzed by XRD (see Figure 1 ), the result is Cu3(BTC)2·H2O. Figure 1 The position of the peak used to determine Cu3(BTC)2·H2O is shown in FIG. The median particle size D of the BTC used is 50 , the total amount of copper hydroxide and BTC, and the amount of methanol used are shown in Table 1. In addition, the peripheral speed, operation mode and number of repeated introductions of the above-mentioned mixer are also shown in Table 1. Furthermore, the volume average particle size and particle size D 10 Relative to particle size D 90 Ratio D 10 / D 90 The volume frequency, angle of repose, degree of compression and BET specific surface area of particles with a volume average particle size of less than 2 μm are also shown in Table 1. "-" in the table means that the measurement was not carried out. The following is a method for measuring the angle of repose and degree of compression.
[0115] <Method for measuring the angle of repose>
[0116] The measurement was performed based on the measurement method described above.
[0117] <Compression Degree Measurement Method>
[0118] The measurement was performed based on the measurement method described above.
[0119] (Comparative Examples 1-2)
[0120] Using copper hydroxide (Cu(OH)2) as a metal ion donor, trimesic acid (BTC) as a multidentate ligand, and methanol as a solvent, the MOF was manufactured in the same manner as in Example 1, except that they were put into a thin film gyratory high-speed mixer (manufactured by PRIMIX Co., Ltd.) at once, and the obtained MOF was cleaned and dried.
[0121] The obtained MOF was analyzed by XRD (refer to Figure 2 ), the result is Cu3(BTC)2·H2O. The peaks used for determination are Figure 1 The median particle size D of the BTC used is 50 , the total amount of copper hydroxide and BTC, and the amount of methanol used are shown in Table 1. In addition, the peripheral speed, operation mode and number of repeated introductions of the above-mentioned mixer are also shown in Table 1. Furthermore, the volume average particle size and particle size D 10 Relative to particle size D 90 Ratio D 10 / D 90 The volume frequency, repose angle, compression degree and BET specific surface area of particles with a volume average particle size of less than 2 μm are also shown in Table 1.
[0122] (Examples 8 to 11)
[0123] The median particle size D of trimesic acid (BTC) as a multidentate ligand is 50 As shown in Table 2, copper oxide (Cu(OH)2) and methanol were put into a thin film gyratory high-speed mixer (manufactured by PRIMIX Co., Ltd.) and the mixture was produced in a circulation manner (continuous manner), i.e., the recovered mixture was continuously introduced from the upper part of the mixer. Except for this, the MOF was produced in the same manner as in Example 1.
[0124] The obtained MOF was analyzed by XRD (refer to Figure 3 ), the result is Cu3(BTC)2·H2O. The peaks used are determined using Figure 1 The median particle size D of the BTC used is 50 , the total amount of copper hydroxide and BTC, and the amount of methanol used are shown in Table 2. In addition, the peripheral speed of the mixer and the number of repeated introductions are also shown in Table 2. In addition, the volume average particle size and specific gravity of the obtained MOF are shown in Table 2. 10 / D 90 The volume frequency, repose angle, compression degree and BET specific surface area of particles with a volume average particle size of less than 2 μm are also shown in Table 2.
[0125] [Table 1]
[0126]
[0127] [Table 2]
[0128]
[0129] As can be seen from Tables 1 and 2, the MOFs in the examples all have a volume average particle size of 1.0 μm or more and 30.0 μm or less, and a particle size D 10 Relative to particle size D 90 Ratio D 10 / D 90 It is 0.35 or more and 1.00 or less.
[0130] Industrial Applicability
[0131] According to the present invention, it is possible to provide a MOF which is a microparticle and has a narrow particle size distribution.
Claims
1. A metal organic structure having a volume average particle size of 1.0 μm or more and 30.0 μm or less, Particle size D 10 Relative to particle size D 90 Ratio D 10 / D 90 It is 0.35 or more and 1.00 or less.
2. The metal-organic structure according to claim 1, wherein The volume frequency of particles with a particle size of less than 2 μm is 20% or less.
3. The metal-organic structure according to claim 1 or 2, which has an angle of repose of 50° or less. The metal-organic structure according to claim 1 or 2, which has a degree of compression of 50% or less. 5 . The metal-organic structure according to claim 1 , comprising at least one metal ion selected from the group consisting of alkali metal ions, alkaline earth metal ions, transition metal ions, Group 13 element ions, and rare earth element ions.
6. The metal-organic structure according to claim 5, wherein: The metal ions include at least one metal ion selected from the group consisting of copper ions, iron ions, zinc ions, zirconium ions, aluminum ions, cobalt ions, magnesium ions, calcium ions, nickel ions, chromium ions, hafnium ions, and lanthanum ions.
7. The metal-organic structure according to claim 1 or 2, comprising at least one organic compound selected from trimesic acid (BTC), terephthalic acid (BDC), isophthalic acid, 2-methylimidazole, 2-5-dihydroxyterephthalic acid (dobdc or DHTA), 4,4'-dioxo-3,3'-biphenyldicarboxylate (dobpdc), fumaric acid, formic acid, 1,3,5-tris(4-carboxyphenyl)benzene (BTB), 4,4'-biphenyldicarboxylic acid (BPDC), oxalic acid, 1,2,4-triazole and 3,5-pyrazoledicarboxylic acid (H3PDC).
8. The metal organic structure according to claim 1 or 2, wherein the BET specific surface area is 100 m 2 / g and above 10000m 2 / g or less.
9. A method for producing a metal organic structure, comprising a centrifugal shearing step of simultaneously applying centrifugal force and shear force to a mixture comprising a metal ion donor, a multidentate ligand and a solvent, The method for producing a metal-organic structure includes a step of recovering the mixed material supplied to the centrifugal shearing step and supplying the mixed material to the centrifugal shearing step again.
10. The method for producing a metal organic structure according to claim 9, wherein: The number of times of the centrifugal shearing step is 3 or more and 10 or less.
11. A method for producing a metal organic structure, comprising a centrifugal shearing step of simultaneously applying centrifugal force and shear force to a mixture comprising a metal ion donor, a multidentate ligand and a solvent, wherein: The median particle size D of the multidentate ligand is 50 It is not less than 0.1 μm and not more than 50.0 μm.
12. The method for producing a metal organic structure according to claim 11, wherein: The number of times of the centrifugal shearing step is 1 or more and 10 or less.
13. The method for producing a metal organic structure according to claim 9 or 11, wherein: The centrifugal shearing step uses a reaction container equipped with a rotary blade, and the peripheral speed of the rotary blade is 10 m / s or more and 100 m / s or less.
Citation Information
Patent Citations
Method for producing metal-organic structure
EP3971160A1
High-speed stirring device
JP2007125454A